PEMIKIRAN KEAGAMAAN TAREKAT NAQSYABANDIYAH DI DESA SUKADATANG KECAMATAN CURUP UTARA KABUPATEN REJANG LEBONG - Kadar Najmiddin (Sekolah Pasca Sarjana IAIN Bengkulu, 2016)
Abstract: Religious Thinking of Naqshbandi Order in the Village of Sukadatang Disctrict of North Curup Rejang Lebong;This research is motivated by the controversy over the existence of followers of Naqsyabandiyah Sufism in in the village ofSukadatang district Rejang Lebong. The problems of this research are: 1).What are the factors supporting the growing followers ofNaqsyabandiyah order in the village ofSukadatang Northern Curup District of Rejang Lebong? 2) How does the practice patterns of thought and religious viewof the Naqsyabandiyah followers in the village ofSukadatang Northern Curup District of Rejang Lebong?. This research is a field research. Data collection techniques used were interviews with informants who directly related to the issues. The results showed that the factors supporting the growing follower of Naqsyabandiyah sufi orderin the village of Sukadatang Northern Curup District of Rejang Lebong are; Firstly, the internal factors of the sufi order which include; the spiritual needs of the congregation followers, leadership figures, regeneration is good, adequate building facilities, and the majority of the followers are middle income. Secondly, is the external factors which include; the support of the Government, JATMI, the Indonesian Ulema Council, and the public. As for the practice of SufiNaqsyabandiyah worshipers in the village of Sukadatang are: repentance bath, allegiance, mysticism, perform dhikr latha’if, and tawajuh. While the religious thought of this order is the moral approach, because the whole practice and dhikr undertaken aim to cleanse themselves of all sins and reprehensible nature. According to them, each participant shall make suluk allegiance to teachers or tutors. About genealogy, the teachings of this sufi order must have a pedigree that can be justified, and how to connect communication between pedigree it could have been through communication with a pedigree who has died, for example through dreams.